Les sanctuaires du Djebel Nefousa - Basset, René (Journal asiatique, 1899)
Text and translation of Shammākhī: Siyar, 598-600. Pp. 434-436, Arabic text. Each of the 97 translated items is enriched with many elaborate annotations and references. On pp. 427-433 Basset gives a chronological survey of governors and dynasties in Ifrīqiyā, parallel to Imams and governors of Nafūsa and Imams of Tāhert.
Keywords: Prosopographie – Djebel Nefousa

Etude sur la Zenatia du Mzab de Ouargla et de l'Oued-Rir' - Basset, René (Leroux, 1892)
Keywords: Linguistique

Loqmân berbère : texte et transcription, avec quatre glossaires et une étude sur la légende de Loqmân - Basset, René (Leroux, 1890)
Fables 3, 23 et 25
Keywords: Linguistique

Les manuscrits arabes des bibliothèques des zaouïas de Àïn Madhi et de Temacin, de Ouargla et de 'Adjadja - Basset, René (Bulletin de Correspondance Africaine, 1885)
Keywords: Manuscrits – Ouargla

Notes de lexicographie berbère - Basset, René (Impr. nationale, 1885)
Keywords: Linguistique

Les sanctuaires du Djebel Nefousa - Basset, René (Journal asiatique, 1899)
Text and translation of Shammākhī: Siyar, 598-600. Pp. 434-436, Arabic text. Each of the 97 translated items is enriched with many elaborate annotations and references. On pp. 427-433 Basset gives a chronological survey of governors and dynasties in Ifrīqiyā, parallel to Imams and governors of Nafūsa and Imams of Tāhert.
Keywords: Prosopographie – Djebel Nefousa

Mission de M. Basset dans le M'Zab et à Ouargla - Basset, René (Bulletin de Correspondance Africaine, 1885)
Keywords: Linguistique – Mzab

Notes de lexicographie berbère : Dialectes du Rif, de Djerbah, de Ghât, de Kel-Ouï - Basset, René (Journal asiatique, 1883)
Keywords: Linguistique

Mission de M. Basset dans le Mezab et à Ouargla - Basset, René (Bulletin de Correspondance Africaine, 1885)
Keywords: Linguistique – Mzab

Lettre de M. Basset au rédacteur du Journal asiatique - Basset, René (Journal asiatique, 1885)
Keywords: Atfiyyash; Muhammad b. Yusuf (1821-1914); Judaïsme – Mzab; Linguistique – Mzab

Un voyage en Tunisie - Basset, René (Bulletin de la Société de Géographie de l’Est, 1882)
Keywords: Linguistique

Review: Chansons berbères de Djerba - Basset, René (Revue des traditions populaires, 1898)
Keywords: Recension

Review: Description et histoire de l’île de Djerba traduite du manuscrit du chikhr Mohammed Abou Rasse Ahmed en-Naceur - Basset, René (Bulletin de Correspondance Africaine, 1885)
Keywords: Recension